A power quality monitoring system based on MATLAB server pages - Vural, Buelent; Kizil, Ali; Uzunoglu, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2010)
The power quality (PQ) requirement is one of the most important issues for power companies and their customers. Continuously monitoring the PQ from remote and distributed centers will help to improve the PQ. In this study, a remote power quality monitoring system for low voltage sub-networks is developed using MATLAB Server Pages (MSP). MATLAB Server Pages, which is an open source technical web programming language, combines MATLAB with integrated J2EE specifications. The proposed PQ monitoring system uses the MATLAB HTML tag library and the data captured by the DAQ hardware to evaluate the Power Quality parameters. The proposed system can be modified as technology and evaluation methods improve.
Keywords: Analyzer; data acquisition; harmonics; microcontroller; PQ monitoring; MSP; power quality; Computer Science; Engineering